Genetic diversity assessment of Georgia peanut cultivars developed during ninety years of breeding. Issue 3 (5th September 2021) - Brown, Nino; Branch, William D.; Johnson, Matthew; Wallace, Jason
Abstract: The cultivated peanut( Arachis hypogaea L.) has experienced severe genetic bottlenecks over the course of its evolution and domestication. Most genetic diversity studies in peanut have focused on global genetic stocks, wild accessions, and related species, but few have focused on elite cultivars. The objective of this project was to assess the genetic diversity of 32 peanut cultivars developed by the University of Georgia breeding program since its inception in 1931. Quantifying genetic similarity (GSIM) among these cultivars will provide a better understanding of their relationships and aid in breeding for cultivar development. Genotyping‐by‐sequencing (GBS), in concert with the recently published A. hypogaea genome sequence, was used to identify a total of 27, 142 single nucleotide polymorphisms (SNPs) among these cultivars. Coefficients of parentage (CoP) were calculated based on publicly available pedigree information and compared with SNP‐based GSIM estimates; the resulting correlations were low, ranging from R 2 = 0.212–0.279. Although genetic diversity is generally low in cultivated peanut, our data indicate that the genetic diversity of Georgia cultivars has actually increased since the early days of the breeding program, likely a result of the incorporation of diverse germplasm and breeding lines into the program. The results reported here provide a valuable understanding of genetic variation among elite Georgia peanut cultivars that have had a significant impact on the peanut industry within the United States. Core Ideas: Genetic diversity of peanut cultivars in the Georgia breeding program increased since its inception GBS is an inexpensive but detailed method of evaluating GSIM of elite peanut cultivars A valuable guide for peanut breeders interested in using Georgia cultivars as crossing parents